2009 IEEE 17th Signal Processing and Communications Applications Conference 2009
DOI: 10.1109/siu.2009.5136444
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HOG algorithm for real time object recognition applications on FPGA based embedded system

Abstract: Özetçe HOG algoritması son yıllarda kompleks içerikli görüntülerde nesne tanıma işlevini yüksek başarım ile gerçekleştirebilen bir algoritma olarak kullanılmaktadır. Bu basit fakat etkin tanımlayıcının donanımsal gerçeklenmesi bir çok temel örüntü tanıma işlevinde kullanılabilirliği söz konusu olduğundan önemlidir. Bu çalışmada HOG algoritmasının, farklı geometrik şekilleri yüksek bir başarım ile tanıyabilen donanımsal uyarlaması FPGA üzerinde gerçekleştirilmiştir. İncelenen görüntü içerisinde geometrik şeklin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In this study, a computationally light but powerful robust method, based on histogram of oriented gradients (HOG) and average magnitude difference function (AMDF), is proposed. Although a similar line of studies is reported in the literature [5,9,13], which employ HOG for shape detection, we are proposing a new hardware-friendly algorithm, which employs AMDF as an effective and easy-to-implement decision module on FPGA. The method uses a set of features extracted from the HOG module, which is later classified by the AMDF module as explained in [14][15][16].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this study, a computationally light but powerful robust method, based on histogram of oriented gradients (HOG) and average magnitude difference function (AMDF), is proposed. Although a similar line of studies is reported in the literature [5,9,13], which employ HOG for shape detection, we are proposing a new hardware-friendly algorithm, which employs AMDF as an effective and easy-to-implement decision module on FPGA. The method uses a set of features extracted from the HOG module, which is later classified by the AMDF module as explained in [14][15][16].…”
Section: Introductionmentioning
confidence: 83%
“…(4). In order to avoid the nonlinear arctangent operation for the angle calculation, several approximation methods are proposed such as 'piece-wise' [5], 'look up tables' (LUT) [10], and 'CORDIC' [20]. As the accurate calculation of the HOG values mainly depends on the angle of the gradient, θ xy , the angle calculation is highly important for the performance of the proposed method.…”
Section: Simulation Of the Methods In Matlabmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on the implementation of HOG-based object detection are limited to either hardware implementations [8], [9], [13] or specific parts of HOG algorithms [1], [20]. There is even no quantitative investigation of what implementation issues could prevent HOG-based object detection from being deployed in real-world applications.…”
Section: Introductionmentioning
confidence: 99%